RE-IRRADIATION AFTER PALLIATIVE HEMOSTATIC RADIOTHERAPY IN BREAST, CERVICAL, AND HEAD-AND-NECK CANCERS: A NARRATIVE REVIEW AND PRACTICAL GUIDE - Biswas, Dr Swarnendu; Kundu, Dr. Pinki (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Hemostatic radiotherapy (hRT) achieves rapid control of tumor-related bleeding across primary sites using short, hypofractionated schedules (e.g., 8 Gy × 1; 20 Gy × 5; 30 Gy × 10). However, re-bleeding and local progression can necessitate re-irradiation (re-RT), posing cumulative dose and toxicity challenges. PMCAnnals of Palliative MedicineObjective: To synthesize contemporary evidence on the safety, efficacy, and technique of   re-RT following prior h-RT in breast, cervical, and head-and-neck cancers, and to provide pragmatic recommendations for low- and middle-income settings.Methods: Narrative review of recent reviews, site-specific series, and guideline-adjacent literature on h-RT and re-RT, emphasizing bleeding control, re-bleeding risk, organ-at-risk (OAR) constraints, carotid blowout risk, and technique selection (EBRT, IMRT, SBRT, brachytherapy). AmegroupsBioMed CentralPMCResults: h-RT provides primary bleeding control in ~80–95% across sites with similar control from 8 Gy × 1, 20 Gy × 5, and 30 Gy × 10; anticoagulation predicts poorer hemostasis. Re-RT can re-establish control in selected patients, with technique tailored to prior dose, interval, target geometry, and proximity to critical vessels/mucosa.                    Head-and-neck re-RT carries a small but catastrophic risk of carotid blowout;  cervical re-RT (often with image-guided EBRT or brachytherapy) is feasible but fistula risk rises with central pelvic re-irradiation,                                                                                 Chest-wall/breast re-RT is commonly feasible and may palliate fungation/bleeding. Conclusions: Re-RT after prior h-RT is reasonable for carefully selected patients with         re-bleeding or symptomatic progression, provided cumulative dose accounting, realistic goals of care, and vascular/mucosal risk mitigation. Standardized prospective data are needed; this review offers a practical algorithm for decision-making. Amegroups